How should local governments tax local business? Lessons from an international comparison and a microsimulation analysis for Germany - Frank M. Fossen; Stefan Bach (Deutsches Institut für Wirtschaftsforschung (DIW), 2007)
The local business tax as the main revenue source of local governments in Germany has been under extensive debate for decades. Proposals for reform range from a broad tax base in the sense of an origin-based value-added tax to a pure profit tax that could be implemented as a surcharge on corporation and personal income tax. Local business taxation systems in OECD countries actually represent the whole spectrum between these two extremes. We use a newly developed microsimulation model for the business sector in Germany to analyse the fiscal and distributional effects of the general reform options identified, including the extension of the local business tax to liberal professionals. We also analyse the effects of the actual German business tax reform 2008 with respect to local business tax revenues.
Keywords: H71; H25; C8; 330; Local business tax; microsimulation; local taxation; tax reform; Gewerbesteuer; Gemeindesteuer; Unternehmensbesteuerung; Steuerreform; Steuerinzidenz; Steueraufkommen; Mikrosimulation; Deutschland